Research trends in sports sciences in Indonesia: A bibliometric analysis - Jumareng, Hasanuddin; Setiawan, Edi; Supriyadi, Edi; Sugiarni, Rani; Abdullah, Khairul Hafezad; Gazali, Novri; Ridwan, Mochamad; Demir, Gí¶ní¼l TekkurÅŸun; Hofmeister, Martin (Jurnal Keolahragaan, 2024)
This study presents a comprehensive bibliometric analysis of research trends in the field of sport science in Indonesia. Using a bibliometric approach, 128 relevant articles were collected, consisting of articles published in journals, written in English, and originating from Indonesia. This research focuses on analysing publication patterns and trends, with particular emphasis on publication year, affiliated institutions, and leading authors in the field of sport science. The analysis showed that 2020 was the year with the highest number of publications, indicating an increased interest and dedication to sport science research in Indonesia during that period. Among the various educational institutions contributing to this field, Universitas Negeri Yogyakarta emerged as the leading campus with the highest number of publications, demonstrating its important role in advancing sport-related studies. Additionally, the study identified "Journal of Physics: Conference Series" as the dominant source of documents, signalling its significance in disseminating sports science research in Indonesia. To shed light on the prolific contributors, this study examined authorship patterns. In particular, three authors, Novita Sari Harahap, Yulingga Nanda Hanief, and Ahmad Nasrulloh, emerged as the most prolific in the sport science domain, with each of them writing four documents in the form of articles. Their notable contributions demonstrate their expertise and dedication to advancing knowledge in the field of sports science. In conclusion, while the current landscape of sport science research in Indonesia shows promise and progress, there are still limitations and areas for improvement. By addressing these challenges and embracing innovative research agendas, the field can continue to develop and flourish, ultimately contributing to the advancement of sport science knowledge and practice on both a local and global scale.